Progress in parasitology - Mehlhorn, Heinz; SpringerLink (Online service). (Heidelberg Springer, 2011)
Parasites threaten the health of animals and humans alike. Especially in times of increasing globalization and global warming, parasites can enlarge their ?kingdom? by spreading. At the same time many of the existing medical products have become ineffective. As these products have been used for many decades, parasites have developed resistances, so that they have progressed in their fight for survival. Therefore it is obvious that humans must develop new methods to face these dangers.  Thus parasitological knowledge increases daily and must be formulated to be accessible for as many parasitologists (veterinarians, physicians, biologists) as possible. Therefore it is necessary that reviews reflecting the present status of the progress in many fields of research be published. Therefore this book, published on the occasion of the 50th anniversary of the German Society of Parasitology, compiles 18 reviews on recent ?hot topics,? including a new vaccine against malarial parasites; severe diseases with poor chances of treatment (cryptosporidiosis, coccidiosis, theileriosis); vectors (mosquitoes, ticks) and their transmission activities; and fish parasites, including molecular insights into the sex of parasites with a focus on the survival abilities that made them so dangerous. These chapters provide detailed information for researchers, as well as for teachers and students in parasitology.
50 years Parasitological Societies in Germany I. Developments in West Germany -- 50 years Parasitological Societies in Germany II. Developments in East Germany -- PROTOZOA -- The world record of parasites in their fight for survival -- Cryptosporidium parvum: The veterinary perspective -- Neonatal porcine coccidiosis -- Posttranslational modifications in apicomplexan parasites -- Development of the RTS, S/A vaccine from concepts to phase III -- Small ruminant theilerosis Interactions of Trypanosoma cruzi and triatomines.-HELMINTHES -- What's about sex in schistosomes ? signaling mechanism in the female gonads Anisakid life cycles and distribution: Increasing zoonotic potential in the time of climate change? -- Fish parasites as biological indicators in an changing world: Can we monitor environmental impact and climate change? -- VECTOR TRANSMITTED DISEASES -- Infectious diseases under the influence of changing environmental factors -- Arthropod vectors and their growing importance in Europe -- A look at the world of ticks -- What else besides TBE and borreliosis? Tick-transmitted pathogens in Germany and beyond -- Tick-borne encephalitis. From microfocus to human disease.
Electronic reproduction.
Keywords: Parasitology; Medical parasitology; Parasitic diseases; Parasites -- Parasitology; Parasitic diseases -- Parasitology; Arthropod vectors -- Parasitology; Electronic books